The effect of the menstrual cycle on the coordination variability of pelvic-hip rhythm during the roundhouse kick executed by female elite taekwondo players - Sajjadi, S. S.; Aziminia, M.; Abbasi, A.; Tazji, M. K. (Research in Sport Medicine and Technology, 2025)
Introduction During the menstrual cycle, the body experiences fluctuations in sex hormones, which can affect performance and injury rates in women. In the integrated human body system, the coordination between joints and limbs influences each other and the ultimate goal of movement.